Interdisciplinarity in university education of graphic design: between theory and practice - Morales Holguín, Arodi (2021)
The tendencies in the university education of design, emphasize the contribution of other disciplines as a promoter of indispensable knowledge for professional practice. Specifically, graphic design is located as a field that demands an interdisciplinary training base according to its dynamics of action. Through the application of a questionnaire to 126 university professors in Mexico, the relevance of graphic design to link up with other disciplines is analyzed, in correspondence with teaching actions carried out. The results show a dilemma between the importance granted to interdisciplinarity versus the low level of commitment manifested in training, differentiated by types of university. It concludes with the relevance of rethinking the training proposals and essentially promoting education that transcends the confines of the same discipline.